Pentingnya Peran Guru Dalam Mengembangakan Interaksi Sosial Anak Autis Pada Jenjang Sekolah Dasar - Khomalasari, Sinar; Lutfiatin, Dwi Indah (PPSDP Undergraduate Journal of Educational Sciences, 2024)
This research aims to determine (1) the role of teachers in developing social interactions in autistic children; (2) the efforts made by teachers in developing social interactions in autistic children; (3) factors causing lack of social interaction in autistic children. The method used in this research is the Systematic Literature Review (SLR) method which consists of 6 stages, namely: planning, literature search, criteria assessment (inclusion and exclusion), quality assessment, data collection, and data analysis. The results of data analysis show that (1) the role of teachers in developing social interaction in autistic children; a) encouraging, guiding and encouraging autistic children in communicating (2) efforts made by teachers in developing social interaction in autistic children; with a series of strategies in the form of methods, techniques and tactics. Teachers use an approach to autistic children through understanding character with PPI (Individual Learning Program), routine communication with parents, repeated advice and giving rewards and punishments, (3) factors that cause lack of social interaction in autistic children; parenting patterns, environment, playing with peers and use of gadgets. The role of the teacher at school is very important for autistic children because this teacher’s role can improve the child’s communication and social interaction skills. It is very important to give children the social support provided by teachers in the environment around the child. The conclusion from this research is that autistic children require very complex treatment and require the participation and role of teachers in matters related to the development of children’s communication and social interactions.